POTRET BUDAYA HADIDAN: Etos Keagamaan dalam Kultur Living Qur’an Studi di PA. Darul Hadlanah Kota Salatiga - Neny Muthi’atul Awwaliyah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
The culture of Hadidan is an amaliyah worship practice carried out in congregation aiming at wishing for blessings from the recitation. The Qur'an as a guide of life for Muslims and an authoritative source in the realm of social reality has developed in meaning. The development of meaning in the Al-Qur'an means the potential of the Qur'an itself which continues to be studied and preserved in the realms of theoretical and praxis. In the theoretical realm, the Qur’an continues to encounter a reconstruction of understanding. This reconstruction relates to the Qur’an itself, what surrounded the Qur’an when it descended and what the Qur’an contains itself. Those two things do not rule out the possibility for the Qur’an to continue to be developed with diverse fields of science, such as sociology, anthropology, history, and hermeneutics, as the approaches to discover the scientific values of the Qur’an. On the other hand, praxis studies examine how the verses of the Qur'an are understood and practiced. This research examines the reality of the community with the Qur'an, in terms of the community’s reception of recitation practice of  Surah al-Hadid’s verses which have magical and mystical powers. It is due to the fact that the verse practitioners of al-Hadid believe that the verses they read contain values that cannot be explained. Thus, the verses of the Qur'an come to live among the community, but only in the form of recitation and perception. This is tantamount to confining the substantial meanings that the verses contain when interpreted or takwil.